Assessment of acceptance, concerns and side effects towards COVID-19 vaccination among the community: A cross-sectional study from Baghdad, Iraq - Zahraa Albasry; Anmar Al-Taie (Elsevier, 2023)
Introduction: The newly developed and marketed vaccines along with concerns about vaccine safety and long-term side effects has been raised an alarming in the general population. The aim of this study was to assess the rate of acceptance, perceptions and concerns towards receiving COVID-19 vaccines and to explore the incidence of vaccines' side effects among Iraqi population in Baghdad province, Iraq. Method: This was a descriptive, cross-sectional study conducted via direct interviews among a convenient sample size of Iraqi population using a structured validated questionnaire consisting of using 24-item questionnaire to assess acceptance, concerns and the incidence of vaccines' side effects towards receiving COVID-19 vaccines. Results: A total of 500 participants with an average age of 27.8 ± 3.7 years were included. Majority were females (70.6%). 43.4% had a history of COVID-19, and 46% received the Pfizer BioNTech vaccine. 73.4% (P < 0.0001) agreed about the importance of receiving the vaccination to protect the community against the COVID-19.46.8% (P < 0.0001) were unsure about the adverse effects and long-term vaccine safety. 72.8% reported that transmission of COVID-19 infection to family members is the main concern for accepting vaccination. Fatigue (60%), injection site reactions (55.8%) were the most common vaccine's side effects. Young age (P = 0.001), females (P < 0.0001), and university educational (P < 0.0001) were the most significant determents for accepting vaccination. Conclusion: This study highlights that the Iraqi population showed a considerable acceptance rate for the COVID-19 vaccines. However, vaccine safety is considered a high priority concern associated with the willingness of the population to vaccinate.